Communication Strategies in Lmplementing the 3Rs Mobius Programme (Reduce, Reuse, Recycle) in Malaysian Secondary Schools - Ismail, Russlan (1999)
To our grandparents, or appropriately most of our parents, learning the 3Rs in school meant Reading, 'Riting and 'Rithmetics - but now there's a new 3Rs being taught in secondary school classrooms throughout Malaysia - Reduce, Reuse and Recycle, thanks to an innovative approach to environmental education that pairs the expertise of business with education goals. The MOBIUS Curriculum: Understanding The Waste Cycle, introduced by the UMW Group in collaboration with the Curriculum Development Centre, Ministry of Education, is currently being used to teach students on the importance of an integrated waste disposal system and how they can help solve the world's growing waste disposal problem by reducing, reusing and recycling. As there are no textbooks on environmental education, the introduction and free distribution of the MOBIUS book to all secondary schools in the country, is considered as timely. In line with that, this study will explore the various communication strategies used by the teachers in implementing the 3Rs MOBruS Programme in our secondary schools, in order to gauge whether the programme is successful and popular among the students. Equally important is whether the communication strategies used by the teachers in the classroom could generate better understanding of the programme among students; or instead, will there be any teaching/learning problems encountered by both the teachers and students. It will also determine whether the level of knowledge and awareness of environmental issues for both teachers/students has increased with the teaching/learning of the programme. And last but not least, is it possible that the level of effectiveness of communication strategies in the classroom will help to increase both the teachers/students' level of knowledge of the 3Rs MOBruS Concept, as well as their level of knowledge of environmental issues and general perception towards the environment.Based on the research survey of 1 43 respondents from both the teachers and students, the [mdings showed that the most traditional method of them all, ie face-to-face communication between teachers and students is the most effective way of communicating and disseminating the contents and concept of the programme to the students. It also showed that both teachers and students were agreeable to the fact that the programme was indeed beneficial to both parties. From the [mdings, we could conclude that there was a clear indication that the awareness on the preservation of the environment and the importance of recycling has also increased. The [mdings also revealed that both the teachers/students ' knowledge of the issues relating to environment has increased after they were introduced to the programme. At the same time, their caring attitude towards the environment has also increased after learning and getting exposed to MOBIUS . It also proved that the relationship between the level of knowledge of the 3Rs MOBIUS Concept with the level of effectiveness of communication strategies in the classroom and the level of knowledge of environmental issues were in fact interrelated, and without one of these elements, the MOBIUS Programme would and could never be a success, even though from the survey it was found that the concept of recycling overshadowed the name of the programme.